(untitled) (Marketing Journal, 2026)
Abstract This article scientifically investigates the issues of developing small business and entrepreneurship in the socio-economic development of regions of Uzbekistan. The purpose of the research is to analyze the current state of small business and entrepreneurship development in the regions, identify problems, and develop scientifically based solutions. Statistical analysis, correlation analysis, SWOT analysis, comparative analysis, and expert survey methods were used. The results show that despite the rapid development of small business and entrepreneurship in Uzbekistan, there are a number of challenges in financing, infrastructure, human resources training, and digitalization. The article proposes an improved model for developing small business and entrepreneurship, an innovative cluster approach, and a digital transformation strategy. Keywords: small business, entrepreneurship, regional development, socioeconomic development, innovation, cluster approach, digital transformation, financing, business environment, Uzbekistan.